Penggunaan Tame Ni dan You Ni Dalam Kalimat Bahasa Jepang - Choirunisa, Hanas; Surono, Surono; Astuti, Setio (Japanese Literature, 2015)
Tame ni in Japanesse language indicates the purpose. Tame ni has the meaning “to” in the Japanesse language sentence usually followed by a verb wich has the intention and desire called ishidoushi. You ni in Japanesse language indicates the purpose. You ni in the Japanesse language sentence usually followed by a verb wich is does not contain the desire called muishidoushi. Author choose this issue because of the dificulty of distinguishing the use of this two words because in Indonesia language have similiar meaning but different in use. The purpose of  this research is to make easy for applying the use of conjungtions tame ni and you ni gramaical structure and meaning Japanesse language sentence.